PRODUCTION OF FLY ASH BASED GEOPOLYMERS USING ACTIVATOR SOLUTION WITH DIFFERENT Na2O AND Na2SiO3 COMPOSITIONS - Azevedo, Adriano Galvão; Strecker, Kurt (Revista Tecnológica, 2018)
In this work, samples of geopolymers were produced by the activation of fly ash with different alkaline solutions (NaOH and NaOH + Na2SiO3). The mechanical strength and microstructural characterization were employed to study the influence of the geopolymerization process in the final proprieties of the binder material. The results showed that the geopolymers have high mechanical strength in the first 24 hours of curing (28 MPa) increasing to 48 MPa after 28 days. The physical proprieties such as water absorption, apparent porosity, and density changed when different solutions were used. The SEM images showed a denser morphology with aluminosilicate gel formation on the surface which is responsible by an increase of mechanical strength of fly ash based geopolymers.